Tinjauan Kuat Tekan dan Kuat Lentur Dinding Pasangan Batu Bata Dengan Perkuatan Diagonal Tulangan Baja - Eka Wahyudianto, Bayu; , Muhammad Ujianto, S.T., M.T; , Yenny Nurchasanah, S.T., M.T (2016)
Most of the Indonesian buildings using a conventional wall or brick as a building wall because in addition to readily available and have a low prices, bricks have a nature that is resistant to high temperatures. Brick walls require modification or retrofitting to increase the strength of a brick wall. Brick wall that has been reinforced by concrete beams with diagonal steel reinforcement is considered possible to add positive value masonry walls and can minimize the damage caused by natural disasters or accidents that occur on the wall. Especially on the brick wall of 1 floor simple house buildings. This research is aims for determine how much the compressive strength and flexible strength of a brick wall without diagonal reinforcement steel and a brick wall with diagonal reinforcement steel . Reinforcement steel is a material that has a high tensile strength and have a good flexible strength. In this research, steel reinforcement were applied with 0.45 of cement water factor (fas).The variation of samples are 5 pieces of cylinders concrete with 30 cm of height and 15 cm of diameter, 5 pieces of cubes mortar with 5 cm of length, 5 cm of width and 5 cm of height, and 24 pieces brick walls with 100 cm of length, 50 cm of width and 12 cm of height . From the research conducted at the Laboratory of Building Materials, Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Surakarta. From the test results of compressive strength of mortar compressive strength values obtained an average of 8.55 MPa, while in this research when the compressive strength testing of a brick wall without diagonal steel reinforcement has an average of 0.919 MPa and a brick wall with diagonal steel reinforcement has an average compressive strength 1,167 MPa, the results of this research is using a diagonal steel reinforcement has a high compressive strength. the strength flexible testing of a brick wall with no diagonal reinforcement steel has an average value of 2.605 MPa and the average value of the flexible strength of a brick wall with diagonal reinforcement steel amounted to 4.452 MPa, the results of these research use a steel diagonal reinforcement has more high value of strength flexibility. From the test result we can conclude that the brick wall with diagonal steel reinforcement is suitable use for simple building in the Indonesian country that frequent of the earthquake disasters, because the compressive strength and flexible strength were quite good. Keywords : Brick Wall, Compressive Strength, Flexible Strength, Diagonal Steel Reinforcement.